Supporting Literacy of English Language Learners in Mainstream Classrooms - Firman Parlindungan; Refanja Rahmatillah (Universitas Teuku Umar, 2020)
English language learners (ELLs) may not yet be proficient enough to participate in a mainstream classroom in the U.S. schools, and they often feel anxious, frustrated, and embarrassed. Identifying best instructional practices to foster literacy learning of ELLs has been an urgent priority in research given the fact that the ELLs population continues to increase. Teachers in the U.S classrooms need to be equipped with sufficient knowledge and skills to meet the needs of these students. In this paper, current understanding of teaching literacy to ELLs in elementary classroom is presented, which revolve around discussion of oral language, complex text, and teacher engagement which is both culturally and linguistically relevant.